Symptoms and strategies in heart failure in Turkey - OĞUZ, SIDIKA (WILEY-BLACKWELL, 2008)
Patients with heart failure can live longer and achieve a better quality of life by learning about the symptoms and management of the disease and about associated changes required in the lifestyle and by controlling symptoms. The objective of this study was to determine the symptoms experienced by patients with heart failure and to identify the strategies they use in the management of the disease. The study was carried out with 64 (53.3%) of patients diagnosed with chronic heart failure [functional class (II-III)] who had been admitted to the cardiology polyclinic. The patients had to be literate and conscious, and had to voluntarily accept to participate in the study. Data were gathered by a questionnaire. The patients were interviewed face to face with the researcher in the polyclinic. Data were evaluated by percentage values, averages and chi-square. Symptoms identified in the subjects were fatigue in 67.2%, dyspnoea in 60.9% and palpitation in 59.4% of respondents. A statistically significant difference was noted between men and women in the case of fatigue (P = 0.039), with this symptom having a stronger restricting effect on the daily activities of men compared with women. A significant difference between men and women was also observed for the management of dyspnoea (P = 0.004), preferred approach for avoiding this symptom being resting for men, while using medication and oxygen for women. Fatigue was found to be the most common symptom experienced by the subjects, followed by dyspnoea, palpitation and oedema, respectively. A significant difference between men and women was noted in approaches for reducing symptoms.
Keywords: Heart Failure; Nursing; Self-Management; Symptoms; Turkey; QUALITY-OF-LIFE; SELF-CARE; MANAGEMENT